The genetics of French Canadians - Brais, Bernard; Desjardins, Bertrand; Labuda, Damian; St-Hilaire, Marc; Tremblay, Marc; Vezina, Helene (Henry Stewart Talks, 2007)
Founder effect, Population history and the French Canadian founder effect, The contemporary population in relation to its founders, Regional gene pools: the examples of the Saguenay and the Gaspesie regions, Regional distribution of disease mutations